Humanização da assistência prestada à parturiente pela equipe multiprofissional do Centro de Parto da Maternidade Escola Assis Chateaubriand - Mendonça, Aline Maria Carvalho Maia (2015)
The humanization of work constitutes the transformation of institutional culture through the collective construction of ethical commitments and methods aimed at health care and service management in the sense of respect and appreciation of the human being. Watch women at delivery and birth in safety and dignity is a fundamental commitment of all health professionals involved in health care of women. It is aim of this study was to evaluate aspects of the process of humanization in care to pregnant women in labor by the multidisciplinary team of Humanized Birth Center Maternity School Assis Chateaubriand. Cross-sectional study conducted in Humanized Birth Center Maternity Assis Chateaubriand, involving 170 mothers who had their normal deliveries. Having called dependent variable "Humanized Birth" classified by the presence contact skin to skin and breastfeeding in the first hour of life. Analyzed by Stata (version 11.2) program. Approved by the ethics committee at No. 830.275. More than half of the interviewed mothers were older than 20 years, ie, the number of teens who gave birth vaginally was 60 (30.0%), where the majority (64.0%) were in married and / or stable. This study revealed some weaknesses regarding the outcome studied, noting that the Humanized Birth was below 50%. It was observed in the bivariate analysis compared to humanized birth an association with education when less than or equal to 7 years and identified that mothers with low education levels, have a predisposing factor for non-adherence to good practice delivery. In gestational history (multigesta category), obtained a considered relationship with the humanized delivery, noting that when the mother had a previous pregnancy history, are more likely to adopt the beneficial practices that favor to labor and delivery. Having "done forceps" was associated with the humanized delivery, and in an attempt to justify this association, we try to understand the real reason was the size acquired in our sample or unfavorable conditions of mothers. The realization of breastfeeding practices in the first hour of life was lower when compared to skin contact. We conclude that when performed in parallel these practices, the success of favoring the other, so the importance to encourage, help and support in the implementation of them in the immediate postpartum period.